[P258] Optical absorbance properties of PVA-GTA Fricke gel dosimeters irradiated with 6 MV and 15 MV X-rays. (August 2018) - Gallo, Salvatore; Artuso, Emanuele; Brambilla, Maria Grazia; Gambarini, Grazia; Lenardi, Cristina; Lizio, Domenico; Monti, Angelo Filippo; Torresin, Alberto; Veronese, Ivan
Abstract : Purpose: Quality assurance procedures required in the modern radiotherapy would greatly benefit by the development of tissue equivalent dosimeters able of rendering 3D dose profiles with high spatial resolution. In this scenario, Fricke gel (FG), consisting in gel matrices infused with Fricke ferrous sulphate solution combined with xylenol orange, could be good candidates, but some limits have prevented their introduction in clinical practice. Recently, new FG formulations based on gel matrices of poly-vinyl alcohol (PVA) cross-linked with glutaraldehyde (GTA) have shown important decrease of the limitations affecting FGs obtained with gelatin or agarose. Purpose of this study is the characterization of the optical absorbance (OA) and dosimetric properties of PVA-GTA FG dosimeters. Methods: PVA-GTA FG dosimeters were prepared using 9.1 w/w of Mowiol ® -PVA and 26.4 mM of GTA. The dosimeters, placed in spectrophotometry cuvettes (10 mm optical path), were uniformly irradiated using 6 and 15 MV X-rays generated by a Varian Clinac-2100. OA spectra were measured by means of an Agilent Cary-100 spectrophotometer. Dosimetric properties of PVA-GTA-FG dosimeters, such as reproducibility, dose–response, sensitivity, dose-rate dependence and energy dependence, were studied. Furthermore, FG in form of layers (3 mm optical path) were irradiated producing steep dose gradients and used to investigate ferric ions diffusion phenomena by means of sequential light transmittance images. Results: The analysis of the OA spectra of the PVA-GTA-FG dosimeters in the wavelength interval of interest for dosimetry purposes (around 550–600 nm) revealed an intra-batch reproducibility of the order of 1.5%. The OA proved to increase linearly with increasing dose, in the investigated interval 0–15 Gy, if the wavelength used for the analysis is properly chosen. The optical response of the PVA-GT-FG dosimeters was independent of both energy and dose-rate. Furthermore, PVA-GTA matrix enables to achieve ferric ions diffusion rates approximatively 3 times lower than those observed in natural gel matrices. Conclusions: This study confirmed the interesting properties of PVA-GTA FG dosimeters and indicated the best parameters for their optical analysis. Currently, studies are in progress in order to optimize Magnetic Resonance Imaging procedures for the assessment of 3D dose distributions in PVA-GTA FG phantoms.